PENGARUH KARAKTERISTIK AUDITOR TERHADAP AUDIT DELAY (Studi Kasus pada Perusahaan Sektor Consumer Cyclicals Go-public yang Terdaftar di BEI Tahun 2018-2022) - Dihyah Amalia Putri; Tarmizi Achmad (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of audit tenure, auditor switching, and the size of Public Accounting Firms (KAP) on audit delay in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. The research is based on assurance theory, which states that auditors are responsible for providing assurance on financial statements. The research method used is a quantitative approach with multiple linear regression analysis. The data used are secondary data obtained from company annual reports. The sample was determined using purposive sampling, consisting of 141 companies over five years of observation, resulting in a total of 705 data points. The independent variables in this study include audit tenure, auditor switching, and the size of the audit firm, while the control variables are firm size, firm age, and profitability. The results show that audit tenure does not have a significant effect on audit delay. In contrast, auditor switching has a significant positive effect, and audit firm size has a significant negative effect on audit delay.